Pelaksanaan Undang-Undang RI Nomor 22 tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan - Rizki Rumondang & Dermina Dalimunthe (Jurnal El-Thawalib, 2021)
Traffic violation is a condition where there is a mismatch between rules and implementation. The regulation in question is Law of the Republic of Indonesia Number 22 Year 2009 Article 302 concerning road traffic and transportation. This research is in the background because of the traffic problems that often occur in Panyabungan District, Mandailing Natal Regency.The results obtained from this study are the traffic problems that occur in the Panyabungan sub-district due to the habits of public transport drivers who often take the rights of other road users and are not orderly in accordance with Law No. The public is not allowed to park carelessly, tap, pick up and drop off passengers in any place other than the stop, through the road network that is not in accordance with the route permit. Then, there are several factors that cause the implementation of Law Number 22 Year 2009, Article 302 concerning Traffic and Transportation in Panyabungan District, Mandailing Natal Regency, due to the condition of road traffic and transportation facilities. For example, there is no terminal specifically for public transportation, then bus stops that have not reached the target and funding is still lacking.Then to find out the results of this study, researchers used a sociological juridical approach. And the research instrument uses observation, interviews and several document studies including official documents, law books, both journals and articles related to this research.